The Impact of Corruption and Fiscal Policy on Economic Growth in ASEAN Countries - Rizki Apriani; Abdul Bashir; Muhammad Subardin (Universitas Negeri Malang, 2025)
This study investigates the impact of government spending, the interaction between corruption and fiscal levels, government debt, and foreign direct investment on economic growth in seven ASEAN countries. Using the World Development Indicators database in the form of time series from the World Bank and the Asian Development Bank for 2000-2021. The approach used is panel data regression using a fixed effect model. The findings show that government spending and foreign direct investment have positive and significant contributions to the economic growth of seven ASEAN countries. There is strong evidence that the interaction between fiscal levels and corruption can distort the fiscal policy mechanism, thereby inhibiting economic growth. Additionally, there is strong evidence that high government debt causes economic growth to contract. Policymakers must strike a compromise between promoting economic expansion through public expenditure and preserving fiscal stability through debt management. To foster an environment that is favorable to investment, efforts to combat corruption must be constantly carried out. To promote equitable and long-term growth, authorities must also concentrate on enhancing the caliber of infrastructure and human resources.